Impacts of el niño and monsoonal interactions on river water quality and cage aquaculture in the Pahang river, Malaysia - Razali, Muhamad Izzuan; Ramly, Rimatulhana; Abdullah, Azila; Abdul Hadi, Muhammad Syafiq Izzuddin; Nawi, Mohd Firdaus; Afandi, Nadia Sabrina; Ramli, Muhammad Zahir; Miskon, Mohd Fuad (Zibeline International Publishing Sdn. Bhd., 2025)
El Niño-induced warming in the central and eastern Pacific often triggers droughts and deteriorates freshwater quality across Southeast Asia, including Malaysia. This study aims to evaluate the impacts of El Niño and Northeast Monsoon dynamics on river water quality and their implications for freshwater cage aquaculture in the Pahang River. Specifically, it examines three 2023 climatic phases: (1) the Northeast Monsoon (January–March), (2) the El Niño period (April–October), and (3) their combined period (November–December). Monthly sampling across multiple sites (n = 96) was conducted to assess key water quality parameters. During the Northeast Monsoon (Jan–Mar 2023), all measured parameters remained within optimal ranges for freshwater fish, except phosphate levels (0.22 ± 0.11 mg/L). During the El Niño phase (Apr–Oct 2023), mean river temperature rose by 3 °C (28 ± 1 °C) with unionized ammonia at 0.013 ± 0.01 mg/L. The combined El Niño–Northeast Monsoon period (Nov–Dec 2023) demonstrated significant degradation in water quality: total suspended solids reached a maximum of 151.5 ± 93.2 mg/L, and ammonia concentrations increased to 1.08 ± 0.49 mg/L, while temperature fluctuated between 26 °C and 30 °C. These alterations adversely affect fish health by reducing dissolved oxygen levels and elevating nitrogen toxicity. The results highlight the considerable challenges that El Niño poses to the sustainability of aquaculture operations in the Pahang River. The implementation of effective mitigation strategies is imperative to protect the aquaculture sector in the region from climate-induced impacts.